Three essays on international cyber threats: Target nation characteristics, international rivalry, and asymmetric information exchange - Mauslein, Jacob A. (Kansas State University, 2014)
As the Internet is progressively integrated into industrial and defense-related networks around the globe, it is becoming increasingly important to understand how state and sub-state groups can use Internet vulnerabilities as a conduit of attack. The current social science literature on cyber threats is largely dominated by descriptive, U.S.-centric research. While this scholarship is important, the findings are not generalizable and fail to address the global aspects of network vulnerabilities. As a result, this dissertation employs a unique dataset of cyber threats from around the world, spanning from 1990 to 2011. This dataset allows for three diverse empirical studies to be conducted. The first study investigates the political, social, and economic characteristics that increase the likelihood of a state being targeted for cyber threats. The results show that different state characteristics are likely to influence the forms of digital attack targeting. For example, states that experience increases in GDP per capita and military size are more likely to be targeted for cyber attacks. Inversely, states that experience increases in GDP per capita and those that are more democratic are less likely to be targeted for cyber terrorism. The second study investigates the role that international rivalries play in cyber threat targeting. The results suggest that states in rivalries may have more reason to strengthen their digital security, and rival actors may be cautious about employing serious, threatening forms of cyber activity against foes because of concerns about escalation. The final study, based upon the crisis bargaining theory, seeks to determine if cyber threat targeting decreases private information asymmetry and therefore decreases conflict participation. Empirical results show that the loss of digital information via cyber means may thus illicit a low intensity threat or militarized action by a target state, but it also simultaneously increases the likelihood that a bargain may be researched, preventing full scale war by reducing the amount of private information held between parties.
Keywords: Cyber attack; Cyber terrorism; Cyber espionage; Targeting; Interstate rivalry; Crisis bargaining; Political Science (0615)